The Strategy of Tahfizul Qur’an Teachers in Improving Students’ Memorization at MA Muallimin Nahdlatul Wathan Gunung Rajak - Syahdan (Formad English Foundation NTB Jakarta, 2025)
This study explores the implementation and impact of the Tahfidzul Qur’an program at MA Muallimin NW Gunung Rajak, focusing on its historical background, instructional strategies, supporting and inhibiting factors, and its influence on students’ character and academic performance. The research employed a qualitative case study approach, using semi-structured interviews with school leaders and teachers, observational data, and document analysis. The data were analyzed using thematic analysis to identify patterns and relationships. The results reveal that the program was initiated as a collaborative effort between the principal and Islamic studies teachers to strengthen students' spiritual foundation and academic discipline. The implementation includes daily Qur’an recitation, structured memorization routines, and character integration. Teachers applied various strategies, such as daily targets, tasmi’, repetition (takrir), and musyafahah, to enhance memorization and spiritual growth. Supporting factors include strong leadership, a religious school environment, and parental involvement, while challenges such as time limitations and inconsistent student motivation persist. Notably, the program has led to significant improvements in students’ discipline, religious behavior, academic focus, and memorization skills. This research highlights the holistic benefits of Qur’anic memorization in character education and academic success. It offers valuable insights for educators and policymakers in developing effective, faith-based learning environments that support student excellence.